Density and distribution of Patella ferruginea in a Marine Protected Area (western Sardinia, Italy): Constraint analysis for population conservation - COPPA, S.; DE LUCIA, G.A.; MASSARO, G.; MAGNI, P. (Mediterranean Marine Science, 2012)
The endemic limpet Patella ferruginea is the most endangered invertebrate of the Mediterranean Sea. Our study examined a population of P. ferruginea in the Marine Protected Area of Penisola del Sinis - Isola di Mal di Ventre (western Sardinia, Italy). During the summer 2009, we carried out a systematic census of P. ferruginea along a 8114 m georeferenced perimeter of coast in the no take-no entry zone to assess its density, spatial distribution, and morphometric characteristics. Our aim was to provide a detailed map of the distribution of P. ferruginea and to investigate the effects of accessibility, wave exposure and slope of the coast on its occurrence. Patella ferrugineashowed the lowest mean density ever reported (0.02 ind/m) and a unimodal population structure characterised by fewer females and juveniles. Accessibility had a major negative effect on the occurrence of P. ferruginea. Exposure was also an important factor in influencing its density, size composition and specimen position within the mesolittoral, while the slope had little influence. Morphometric analysis showed the dominance of the Rouxi form, while the Lamarcki form was confined to exposed sites. Our results demonstrate a highly endangered population of P. ferruginea and suggest that human pressure represents the main risk factor.